Polemik "Tulisan Arab" Pada Busana Agnes Monica (Analisis Teori Interaksionisme Simbolik) - Ihsanudin, Ihsanudin (Palita: Journal of Social Religion Research, 2019)
Arabic is synonymous with the symbol of Islam. Because the Qur'an and Sunnah use Arabic Language. However, tren fashion is now entering the era of globalization. It doesn't matter if tren fashion is currently mixed with western and eastern cultures. Agnes Monica's dress, which when appearing on television shows, attracted controversy of many parties because it was considered taboo, because of the transparent clothing and Arabic writing that was right on her thigh. Various suggestions from nitizen fulfilled the social media homepage, MUI also commented on the polemic that had taken place. The Mead Symbolic Interactionism Theory is very appropriate to be used as a knife for analyzing the case above. The purpose of this study is to describe and analyze the phenomenon of Agnes Monica's dress Arab writing "Al-Muttaá¸¥idah" using Mead's theory, include describing the specifically human social act, action, gesture, signicicant symbols, mean, self, and society. This research is belong to library research andÂ  use analytical descriptive methods.Tren Fashion, Arabic Writing, Mead's Symbolic Interactionism.